STUDI ORIENTASI PELANGGAN TERHADAP KEPUTUSAN MENGAMBIL KREDIT SEPEDA MOTOR MELALUI INOVASI LAYANAN DAN WEB DESIG QUALITY PADA FIFIGROUP CABANG PONTIANAK - Nerika Novi; Lauw Sun Hiong (Department of Management - Institut Shanti Bhuana, 2023)
The goal of the study is to provide a robust framework for understanding how web design quality and the credit applications of motorcycle at FIFGROUP Cabang Pontianak relate to one another. The results of this study were derived from sample responses regarding the reason for extending credit for a second vehicle. For the purposes of this study, a quantitative study was conducted with 154 responses from members of the FIFGROUP Cabang Pontianak as the sample. Purposive sampling and data collection by keystroke logging are the two methods used for sample preparation. The patient is using the version 24 of the computer program Analysis of Moment Structure (AMOS). The results of the SEM (Structural Equation Modelling) study point to the importance of improving customer orientation toward credit applications through innovative service offerings, but not at the expense of web design quality. Results from the uji regression weight are supported by the assertion that orientation.